Emerging uses of computers for education : an overview of tools and issues for vocational educators - Lewis, Matthew W.; Rand Corporation; National Center for Research in Vocational Education (U.S.); University of California, Berkeley; United States. Office of Vocational and Adult Education (Santa Monica, CA : RAND, 1992)
This study, conducted as project of the National Center for Research on Vocational Education (NCRVE), examines emerging computer-based educational technologies and discusses their current penetration into, and potential relevance for vocational education. These tools have powerful capabilities for simulating work environments and complex devices, guiding students interactively, providing access to and manipulation of a rich variety of multimedia reference materials, and linking students and teachers across distances. The study summarizes the reactions of a vocational educator's focus group to the emerging technologies and suggests ways in which vocational educators might participate in shaping the technologies and prepare for their appropriate use.
Includes bibliographical references (p. 57-66).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Educational technology -- United States; Vocational education -- United States -- Data processing